Litterfall-Associated Carbon Deposition and Vertical Profiles of Soil Organic Carbon in Different Land-Use Systems - Mengistu T. Teramage; Biruk Bassango; Getachew Sime (Applied and Environmental Soil Science)
Litterfall is one of the major inputs for soil nutrients. Understanding the connection of litterfall and soil organic carbon (SOC) as the part of ecological processes is a key step towards carbon sequestration as a climate change mitigation strategy. Yet, it remains inadequate to support by empirical pieces of evidence particularly in tropical ecosystems. In this study, litter traps were used to monitor the monthly organic carbon deposition over a year through litterfall, and soil samples were collected vertically up to 30 cm depth to define the SOC depth distribution in three different land use types located at Wondo Genet district, southern Ethiopia. The results were interpreted by deploying both the carbon stratification ratio (CSR) and carbon flow balance ratio (CFBR) as ecological indicators. The results revealed that both the annual litterfall amount and associated organic carbon input in plantation forest (958.4 ± 112 g·m−2·yr−1; 391.4 ± 112 g·C·m−2·yr−1) were higher than those in the homegarden (183.5.4 ± 26 g·m−2·yr−1; 67.4 ± 10 g·C·m−2·yr−1), conceivably due to few litter contributors (trees) present in the homegarden. The CSR of the homegarden (1.3 ± 0.01) was found between the ratio obtained for crop (1.2 ± 0.01) and plantation forest (1.4 ± 0.01), indicating that it is definitely a combination of pure plantation forest and crop system. The CFBR was higher in plantation forest (3.4 yr−1) than in soil of homegarden (0.77 yr−1), implying the net accumulation of soil carbon over time in the latter system. Hence, homegardens could be considered as a system of climate-smart practice with multiple-biogeochemistry pathways, which simultaneously address the social-absolute needs. Given the current tendency of transforming homegarden agroforestry to monoculture types owing to economical drivers, such indicators can dictate of making rational decisions related to land use planning and soil fertility management.